If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + -7 = 3a + 4 Reorder the terms: -7 + 2a = 3a + 4 Reorder the terms: -7 + 2a = 4 + 3a Solving -7 + 2a = 4 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -7 + 2a + -3a = 4 + 3a + -3a Combine like terms: 2a + -3a = -1a -7 + -1a = 4 + 3a + -3a Combine like terms: 3a + -3a = 0 -7 + -1a = 4 + 0 -7 + -1a = 4 Add '7' to each side of the equation. -7 + 7 + -1a = 4 + 7 Combine like terms: -7 + 7 = 0 0 + -1a = 4 + 7 -1a = 4 + 7 Combine like terms: 4 + 7 = 11 -1a = 11 Divide each side by '-1'. a = -11 Simplifying a = -11
| -9t+2=15 | | -3.6+X=-5.2 | | 4(2x-5)=3+8x-11 | | 2/3n+6=n | | 50x^2-100=40x^2 | | -4+m=40 | | 3(y-5)=2+5 | | -(3z^2+4z)-(6z^2-2)= | | 5x-3(x-2)=-6+4x-2 | | -5a-12=6(-2-8a) | | Pq=xforq | | 2(x+1)-5=9 | | 4x+6=2(x-5) | | -7p+7=-8-4p | | 4x-2=2x+7 | | 3.2-.08w=-4 | | 4x+9y=74 | | u(-u^2+14u+32)=0 | | 8x+1=6-2x | | u(-u+14u+32)=0 | | 6-(2x-3)=-5x+18 | | m-4=3m+10 | | 2x^3-30x=0 | | (5x^2-2x-1)-(3x^2-5x+7)= | | -2-b=-6-b | | 20b^2-16b= | | 2(x+5)-3x=8 | | 200=8+7x | | -3+3j=6 | | t^2+16t-200=0 | | 4a-6=38 | | -9y-4=-8y-7 |